A orillas de la Revolución: Martín Luis Guzmán en Madrid (1915) - Quintanilla, Susana (El Colegio de México, A.C., 2014)
1915 is considered a decisive year in world history. Underneath wartime plundering, eighteenth-century beliefs in social progress and human civilization collapsed, and other political and philosophical credos sprouted, while aesthetic avant-gardes created new forms of artistic and literary expression.That same year, from his exile in Madrid, Martín Luis Guzmán would define the coordinates that would guide his life, while trying to assimilate his recent experiences during the Mexican Revolution and make way as a writer, under the immediate protection of Alfonso Reyes and the far-away but determining one of Pedro Henríquez Ureña. Without abandoning his political vocation and remaining open to new trends, Guzmán drew up his own path, which would lead him alongside his mentors and to the forefront of literature in Spanish.